Steam oxidation behavior of Ni-base superalloys 690, 725 and X-750 at 600 and 650 °C. (15th August 2019) - Tan, L.; Chen, T.; Pint, B.A.
Highlights: Distinct behavior exists between the 600 and 650 °C steam exposures. The least metal loss occurred for alloy X-750 at 600 °C while alloy 690 at 650 °C. The steam exposure primarily resulted in Cr-rich oxide with Al2 O3 internal oxidation. The experiment-identified phases generally agree well with thermodynamic calculations. Abstract: The 1-bar steam oxidation behavior of Ni-base superalloys 690, 725, and X-750 was evaluated at 600 and 650 °C for up to 5000 h. In addition to monitoring mass changes, microstructures of the 5000-h-exposed samples were characterized using scanning and transmission electron microscopy and energy dispersive x-ray spectroscopy. Together with thermodynamic calculations, the scale constitution and possible exfoliation was discussed. Alloy X-750 exhibited the best resistance to steam oxidation with the least metal thickness loss at 600 °C while alloy 690 at 650 °C. Alloy 725 exhibited more than two times metal thickness loss than the other two alloys at 650 °C.